Arab Human Development Report 2002 - United Nations Development Programme (United Nations, 2002)
This report, the first regional Human Development Report (HDR) for the Arab States, focuses on the people of the Arab world, particularly the citizens of the 22 member states of the Arab League, from Maghreb to the Gulf. The report shows that Arab countries have made significant strides in more than one area of human development in the last three decades. Nevertheless, it also illustrates the shortcomings in the areas of freedom, empowerment of women, and knowledge. No generation of young Arabs has been as numerous as today. For that reason, the report is especially mindful of the children of marginalized and oppressed Arabs, not excluding the Palestinian children. For that reason, the Report team has dedicated this first issue to coming generations. The report was prepared by a team of Arab scholars, and as such, is a look in the mirror. It is aimed at stimulating discussion and debate by policy-makers, practitioners and the general public on how to best tackle the most pressing challenges to improving human development across the region.